Relationships between Doses and Application Methods of Phosphorus and Corn Nutrition Status and Grain Yield - Lemos, Evandro Freire [UNESP]; Prado, Renato de Mello [UNESP] (Taylor & Francis Inc, 2017)
The broadcast application of phosphate fertilizers may be more effective than localized application methods for the growth of corn in medium textured oxisol, which have lower phosphorus (P) adsorption capacity. This study aimed to evaluate three phosphate fertilizer application methods at five different doses onto corn grown in oxisol, over two seasons. The experiment was conducted on corn crops in Passos city, Minas Gerais state, Brazil. Stripes with split plots were used to investigate the different application methods where each plot represented double furrow, single furrow, or broadcast application. Within the sub plots, the five doses (0.0, 50, 100, 200, and 400 kg ha(-1)) of phosphorus pentoxide (P2O5) as granulated monoammonium phosphate (MAP) were applied. Four replications were used. The doses were reapplied in the second cultivation year only for the localized treatments (single and double furrow). The nitrogen in the MAP was held constant among treatments. The corn grain yield in both years was dependent upon both dose and application method, primarily for the single furrow and broadcast methods. In the first year, the broadcast application method of P fertilizer at a estimated dose of 319 kg ha(-1) of P2O5 provided a greater accumulated yield over two seasons. Broadcast application is therefore a viable method for growing corn with a reduced spacing distribution on medium textured oxisol.
Keywords: Broadcast spread; double furrow; leaf diagnosis; phosphate fertilizing; single furrow